Randomized Study on Early Detection of Lung Cancer with MSCT in Germany: Results of the First 3 Years of Follow-up After Randomization. Issue 6 (June 2015) - Becker, N.; Motsch, E.; Gross, M.-L.; Eigentopf, A.; Heussel, C.P.; Dienemann, H.; Schnabel, P.A.; Eichinger, M.; Optazaite, D.-E.; Puderbach, M.; Wielpütz, M.; Kauczor, H.-U.; et al.
Abstract : Introduction: The German Lung Cancer Screening Intervention Trial (LUSI) is one of the European randomized trials investigating the efficacy of low-dose multislice computed tomography (MSCT) as a screening tool for lung cancer. In the evaluation of the first (prevalence) screening round, we observed exceptionally high early recall rates, which made the routine application of MSCT screening questionable. Because screening may behave differently in subsequent (incidence) screening rounds, we analyzed (a) basic characteristics for the annual rounds 2 to 4, which have now also been completed, and (b) the first 3 years with complete follow-up since time of randomization. Methods: Data material was the data record of LUSI after the fourth screening round and the 3-year follow-up had been completed. Basic characteristics of screening, e.g., early recall rate, detection rate, and interval cancers as well of proportion of advanced cancers, were descriptively evaluated and, if informative, group differences were tested for statistical significance. Results: Early recall rates were significantly lower in the subsequent screening rounds than in the first one if the MSCT information from the previous screening rounds was available. Detection and biopsy rates were approximately 1% or lower, ratio of benign:malignant biopsies: 1:1.6 to 1:3. Conclusion: Our recent data may not only settle one concern regarding high recall rates in routine MSCT screening but also indicate that screening must be strictly organized to be effective. Performance indicators are similar to those in mammography screening. Nevertheless, possible consequences for the participants (diagnostic workup of suspicious findings, biopsies) are more invasive than in mammography screening.